Application of Montessori-based activities in teaching fractions to intermediate students with learning disabilities - Reyes, Careza P. (2008)
This quasi-experimental design study aimed to find out whether Montessori-based activities and the use of its materials are effective in teaching fractions to intermediate students with learning disabilities. This research used Pre-test and Post-test instruments to gather data. Results revealed that there is a significant difference in the pre-test and post-test scores of the participants after being taught fracations using Montessori-based activities. There was no significant difference between the performance of students with language difficulty and attention difficulty, and the participants' attitude towards the use of the Montessori materials.